Relative Influence of Capillary Index Score, Revascularization, and Time on Stroke Outcomes From the Interventional Management of Stroke III Trial - Al-Ali, Firas; Elias, John J.; Tomsick, Thomas A.; Liebeskind, David S.; Broderick, Joseph P. (Stroke (1970), 2015)
BACKGROUND AND PURPOSE—Until recently, acute ischemic stroke (AIS) trials have failed to show a benefit of endovascular therapy compared with standard therapy, leading some authors to recommend decreasing the time from ictus to revascularization to improve outcomes. We hypothesize that improving patient selection using the capillary index score (CIS) may also be a useful strategy. METHODS—CIS was calculated, blinded to outcome, from pretreatment diagnostic cerebral angiograms for 78 subjects in the Interventional Management of Stroke III database with internal carotid artery and middle cerebral artery trunk occlusion. The CIS was dichotomized into favorable (fCIS=2 or 3) and poor (pCIS=0 or 1). Outcomes were categorized based on the modified Rankin Scale score at 90 days (0–2 considered a good outcome). Modified thrombolysis in cerebral infarction score 2b or 3 was considered good revascularization. Multivariable logistic regression was performed to relate CIS, time from ictus to revascularization, modified thrombolysis in cerebral infarction score, and National Institue of Health Stroke Scale score to good outcomes. RESULTS—Only CIS and modified thrombolysis in cerebral infarction scores were correlated with good outcomes (P<0.01). Patients with fCIS and good revascularization achieved 71% modified Rankin Scale ≤2, compared with 13% for patients with pCIS and good revascularization. CONCLUSIONS—In this subset of patients from the Interventional Management of Stroke III Trial, CIS and modified thrombolysis in cerebral infarction were strong predictors of outcome after endovascular reperfusion. Using the CIS to improve patient selection could be a powerful strategy to improve rate of good outcomes in endovascular therapy. A randomized trial is needed. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov. Unique identifierNCT00359424.